2009
DOI: 10.1159/000195540
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Patients on Endocrine Therapy Reveal More Symptoms when Self-Reporting than in Pivotal Trials: An Outcome Research Study

Abstract: Objectives: The purpose of this investigation was firstly to assess the overall frequency of subjectively experienced symptoms self-reported by patients receiving endocrine therapy and secondly to compare these symptoms with side effects assessed by clinicians in pivotal trials. Methods: Unselected patients with early and advanced breast cancer receiving endocrine therapy were approached consecutively during a routine outpatient visit. They received a questionnaire called Checklist for Patients with Endocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Our results, thereby, confirm the presumption that PROs reveal a higher level of symptom burden than conventional pivotal clinical trials [11,12,25,26]. Ruhstaller et al [16] reported comparable results in their PRO-based study. Though differing sample characteristics (i.e., treatment with tamoxifen) precluded direct comparison with our study results, their findings support the notion that the use of PROs leads to reporting of increased symptom frequency.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results, thereby, confirm the presumption that PROs reveal a higher level of symptom burden than conventional pivotal clinical trials [11,12,25,26]. Ruhstaller et al [16] reported comparable results in their PRO-based study. Though differing sample characteristics (i.e., treatment with tamoxifen) precluded direct comparison with our study results, their findings support the notion that the use of PROs leads to reporting of increased symptom frequency.…”
Section: Discussionsupporting
confidence: 86%
“…Although health care providers are supposed to be at the best position to report on toxicity [6], several studies on endocrine strategies in breast cancer treatment [9,[13][14][15] have shown a poor concordance of expert ratings and patient-reported frequencies for treatment-related non-life threatening symptoms. In the only study to date comparing patient-reported outcomes (PROs) in breast cancer patients receiving endocrine therapy with expert ratings [16], numerous symptoms (e.g., hot flushes/ sweats, low energy, and vaginal dryness) have been reported in a significantly higher percentage by the patients than by physicians. There is a lack of prevalence data generated in prospective studies specifically aiming for the assessment of adverse effects in this treatment group.…”
mentioning
confidence: 99%
“…Our PRO study confirms a notably high level of psychosocial burden and physical side effects in premenopausal BC patients undergoing adjuvant TT. Evidence published only recently seems to support these findings claiming higher frequencies of several symptoms when subjectively reported, e.g., hot flushes/sweats or weight gain than known from previous pivotal studies (8). The frequencies of several symptoms herein distinctively exceed the reported frequencies for adverse events for premenopausal women in the ABCSG-12 study.…”
supporting
confidence: 56%
“…Previous studies suggest incorporating patient-reported outcome assessments into follow-up appointments for survivors receiving AET significantly increases symptom reporting [35, 36]. Future research could examine strategies for routinely incorporating patient-reported outcome assessments into sur-vivorship care and optimal implementation such as collecting data at patient check-in and determining how best to organize, present, and respond to patient-reported AET symptoms within electronic health records [37, 38].…”
Section: Discussionmentioning
confidence: 99%